O uso da planilha eletrônica no estudo das funções e equações polinomiais - Mogilka, Marcelo (2016)
The use of technologies as teaching tool is a reality experienced by a significant portion of the student body in Brazil. However, there is still considerable demand for educational projects involving the teaching of mathematics with the technologies offered by computer programs. This work will address - through the Delta Project the usage of electronic spreadsheets as a tool for analysis and resolution of func- tional and polynomial equations, establishing links between the mathematical and computational knowledge.